Enhancing employee innovative behavior: The moderating effects of organizational tenure - Muhammad Anwar Ul Haq; Muhammad Usman; Jawad Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The purpose of this study is to find out that how the innovative behavior of employees can be enhanced and whether it remains same as the organizational tenure of employees increases. We propose that innovativeness among employees may be enhanced through four factors which include perceived failure tolerance, communication openness, work discretion, and reward fairness. Further, we assume that the effect of predictors will be moderated by the organizational tenure of the employees. Data were collected from 381 employees from the telecommunication sector in Pakistan. The application of two step structural equations modeling shows that all the antecedents have positive effect on employee innovativeness. Further, organizational tenure moderates this effect negatively. Employees with lesser organizational tenure were found to be more innovative. We recommend that organizations must establish a culture based on failure tolerance, open communication, work discretion, and fairness in order to cultivate innovative behaviors among employee. Furthermore, special refresher trainings, and lucrative incentives should be given to employees with higher organizational tenure in order to benefit their innovative potential.
Keywords: 330; innovative behavior; perceived failure tolerance; communication openness; work discretion; reward fairness; organizational tenure